Maintaining tree islands in the Florida Everglades: nutrient redistribution is the key. Issue 7 (1st September 2005) - Wetzel, Paul R.; van der Valk, Arnold G.; Newman, Susan; Gawlik, Dale E.; Troxler Gann, Tiffany; Coronado-Molina, Carlos A.; Childers, Daniel L.; Sklar, Fred H.
Abstract : The Florida Everglades is an oligotrophic wetland system with tree islands as one of its most prominent landscape features. Total soil phosphorus concentrations on tree islands can be 6 to 100 times greater than phosphorus levels in the surrounding marshes and sloughs, making tree islands nutrient hotspots. Several mechanisms are believed to redistribute phosphorus to tree islands: subsurface water flows generated by evapotranspiration of trees, higher deposition rates of dry fallout, deposition of guano by birds and other animals, groundwater upwelling, and bedrock mineralization by tree exudates. A conceptual model is proposed, in which the focused redistribution of limiting nutrients, especially phosphorus, onto tree islands controls their maintenance and expansion. Because of increased primary production and peat accretion rates, the redistribution of phosphorus can result in an increase in both tree island elevation and size. Human changes to hydrology have greatly decreased the number and size of tree islands in parts of the Everglades. The proposed model suggests that the preservation of existing tree islands, and ultimately of the Everglades landscape, requires the maintenance of these phosphorus redistribution mechanisms.